Continuous renal replacement therapy is associated with acute cardiac stunning in critically ill patients. Issue 3 (15th May 2019) - Slessarev, Marat; Salerno, Fabio; Ball, Ian M.; McIntyre, Christopher W.
ABSTRACT: Introduction: Intermittent renal replacement therapy induces cardiac stunning in chronic hemodialysis and acute kidney injury (AKI) patients. In chronic hemodialysis, recurrent stunning contributes to heart failure and cardiac death, with ultrafiltration and intradialytic hypotension being the principal determinants of this injury. Continuous renal replacement therapy (CRRT), with its lower ultrafiltration rates and improved hemodynamic profile, should protect against cardiac stunning in AKI. The objective of this study was to assess whether CRRT is associated with cardiac stunning in critically ill patients with AKI. Methods: We prospectively measured cardiac function using global and segmental longitudinal left ventricular strain using transthoracic echocardiography in 11 critically ill patients who were started on CRRT for AKI. We compared measurements at 4, 8, and 24 hours to baseline immediately prior to initiation of CRRT, with each patient serving as their own control. We also recorded blood pressure, heart rate, dose of vasoactive medications and intensive care unit mortality. Findings: Ten of 11 patients developed new regional cardiac stunning, with 8/11 within 4 hours of starting CRRT, despite stable hemodynamics. The number of affected left ventricular segments varied from 1 to 11 (out of 12). The stunning occurred both in patients with preserved and impaired baseline cardiac function, and 7/11 patients died in the intensive care unit. Discussion: Initiation of CRRT in critically ill patients with AKI is associated with cardiac stunning despite stable hemodynamics. This mechanism may explain lack of clinical benefit of CRRT over intermittent modalities and warrants further investigation to improve cardiovascular outcomes in critically ill patients with AKI.